Conceptual approaches to improving water quality of rivers in Cameron Highlands, Malaysia - Pauzi A. (2021)
Water quality of rivers in Cameron Highlands has deteriorated significantly mainly due to input from non-point pollution sources such as land clearing for agriculture, excessive usage of pesticides and fertilisers, construction activities and urbanization. It is caused by the mismanagement and lack of policy enforcement. Unlike point-source discharges, non-point source discharges are relatively complex systems to measure and control. As a result, the current regulatory methods, such as water-quality standards and allowable-discharge permits that are commonly practiced as a gauge to measure and manage point-source pollution are found to be inadequate techniques and generally impracticable for controlling non-point source pollution. Therefore, this study has suggested conceptual non-structural Best Management Practice (BMP) to improving water quality of rivers in Cameron Highlands. Greater emphasis has been given to agricultural activities as the main contributor to water-quality reduction in the area. Authorities’ and public communication as well as awareness via community education were recommended as the most influential approaches followed by the implementation of good agricultural practices, performance of sustainable land management practices and the enhancement of controls on development approval, site planning and construction.